Fatores ambientais e silviculturais na qualidade dos povoamentos e da madeira de teca - Leonardo, Fernanda Viana da Silva (2018)
In silvicultural practice, it is common for management decisions to be made on the basis of quantitative or volumetric production expectations. Such decisions do not always conform to the characteristics required for the final destination of the wood. Tectona grandis L.f. is a large tree species, valued economically because of the quality and beauty of its wood, mainly for use in furniture and shipbuilding. The classification and economic valuation of teak wood have aroused the concern of producers and consumers with their quality. The objective was to evaluate how the environmental and silvicultural factors influence the characteristics of the stand and teak wood. The work was carried out in Figueirópolis D'Oeste, Mato Grosso, with clones from Malaysia and Solomon Islands and plants of seminal origin. Populations were evaluated for mortality, growth, morphometry and response to biotic and abiotic damages. The wood was evaluated for the variation in the production of heartwood and sapwood, considering the different genotypes and faces of wood exposure to solar radiation in relation to the cardinal points. Population data were submitted to descriptive statistics. The variables of individual chopped trees were submitted to main component analysis (PCA), multivariate analysis of variance (MANOVA) and Tukey test at 5% of error probability. Clones of the Solomon Islands are more vulnerable to the wind. The Perlis clone and seminal plants are symptomatic of forest pathogens. The increase in sapwood area is more correlated with the average annual increase in cross-sectional area, except at higher stages of competition between plants. Direct solar radiation does not affect core and sapwood targeting in the intermediate, suppressed, and oppressed classes.